Assessing the Relevance of Multiple Intelligences-Based Learning Methods for Seventh Grade Students - Lisdiyanti, Tika; Maulana, M. Khakim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
An optimal learning environment is one where students feel at ease, enjoy the learning process, and can readily absorb and apply the taught material in their daily lives. This study investigates the suitability of implementing Multiple Intelligences-Based Learning Methods to enhance the learning experience. A qualitative research approach, specifically a case study design, was employed to explore this topic. The findings reveal that the utilization of Multiple Intelligences-Based Learning Methods aligns well with the learning needs of seventh-grade students at MTs Al Hikmah Bandar. This method diversifies teaching and learning activities, effectively capturing students' attention and engagement. By discerning students' preferences and matching them with relevant learning approaches, educators can group students with similar interests. Leveraging these aligned interests and appropriate learning methods results in more effective learning outcomes and the achievement of learning objectives. Ultimately, this approach empowers students to apply their acquired knowledge in their everyday lives.